Horizontal price transmission in Mexico’s dry-bean (Phaseolus vulgaris L.) market - Aguilar-Lopez, Antonio; Melo-Guerrero, Enrique; Martínez-Damian, Miguel Ángel; Hernández-Ortiz, Juan; Valenzuela-Nuñez, Luis Manuel (Ecosistemas y Recursos Agropecuarios, 2024)
Despite the liberalization of agriculture experienced during the recent decades, Mexico is close to self-sufficiency in the case of dry bean. The behavior of the market for this grain is determined mainly by internal factors influencing both demand and supply. In this context, the objective of this paper is to analyze the movement of prices for negro bola bean in Zacatecas and pinto bean in Chihuahua, and the movement of prices for the same varieties available in Mexico City; for this purpose, monthly prices for the period August 2005 – June 2022 were used. The analysis was carried out using econometric methods that determine the presence of horizontal price transmission. The results indicate the presence of cointegration for negro bola bean prices, and causality running in both directions. We also found causality running in both directions for pinto bean, although the prices are not cointegrated.